Immunotherapy-related cardiovascular toxicity: from mechanisms to management - Xiao, Lifeng; Liu, Weitong; Ji, Yanchen; Li, Qiufeng; Pan, Junqing; Xie, Renxian (Frontiers in Pharmacology, 2026)
Cancer immunotherapy, including immune checkpoint inhibitors and CAR-T cell therapy, has revolutionized oncology but is associated with a broad spectrum of cardiovascular toxicities. This review comprehensively examines the current landscape of these adverse events, which range from myocarditis, pericardial disease, and arrhythmias to heart failure. We delve into the underlying pathophysiological mechanisms, such as T-cell-mediated cross-reactivity via molecular mimicry and cytokine-mediated injury in cytokine release syndrome. The article critically appraises strategies for risk stratification, vigilant monitoring using biomarkers and advanced imaging, and management protocols that encompass immunosuppression, targeted biological therapies, and supportive care. Furthermore, we explore the complex interplay with vaccinations and infections and highlight promising future directions, including novel therapeutic targets, preventive strategies, and advanced monitoring technologies. Ultimately, this review underscores the necessity of a proactive and multidisciplinary cardio-oncology framework to mitigate cardiovascular risks while preserving the anticancer efficacy of immunotherapies.